Effects of hydrothermal–microwave treatment on bending properties of teak in plantation - Huang, Donghai; Shen, Huajie; Zhang, Jilin; Zhuo, Xinzhen; Dong, Liangzhou (Frontiers in Materials, 2024)
In order to study the bending properties of tropical tree species rich in organic extracts, the effects of temperature and time on the bending performance of hydrothermal treatment were investigated. The effects of power and time on bending performance under microwave heating conditions were investigated. It is found that the chemical composition does not undergo obvious degradation at 80°C–100°C, and the bending performance gradually becomes better with the increase in heating time; when the hydrothermal time exceeds 4 h, the bending performance varies with heating time. The growth is better than the difference, reaching the maximum at 4 h. When the water temperature is 140°C, the bending performance is negatively correlated with the heating time. When the hydrothermal treatment time is the same, the bending property becomes better as the temperature increases. The most reasonable process for microwave softening heating is with a power of 480 W and a heating time of 4 min. A softening treatment method combining water heat and microwave can achieve a better softening effect. When the final moisture content is controlled to 8%, the bending setting effect is the best. The optimum drying time is 6 h, and the optimum drying temperature is 50°C.